Implementasi Pengelolaan Bantuan Operasional Sekolah Reguler pada Peningkatan Sarana Prasarana dan Kualitas Pembelajaran di SD Yapis Kota Bogor - Nurhayati, Nurhayati; Primarni, Amie; Tholkhah, Imam (Jurnal Dirosah Islamiyah, 2024)
The purpose of this study was to describe the management of Regular BOS at SD YAPIS Bogor City and its impact on improving infrastructure and the quality of learning at SD YAPIS Bogor City.The approach used in this study is a qualitative approach with descriptive methods. The resource person consists of 6 people with positions, Head of school, Deputy Head of Curriculum, Deputy Head of Student Affairs, treasurer, operator and teacher at fifth grade.The results showed that the management of regular BOS increased the infrastructure at SD YAPIS. In 2023 Yapis already has a Computer Lab with 12 sets of computers along with tables and chairs. While in the previous year there were only 6 sets. This also affects the increase in ANBK results. ANBK is an indicator of improving the quality of learning for elementary school level students which is implemented in grade 5 students. From the 2023 Education Report Card, the proportion of students with numeracy skills reaching a minimum competency increased by 42.86%. Where in 2022 it will be 23.33 and in 2023 it will be 33.33. Keywords: Management of Regular BOS, Infrastructure and Learning Quality